2014
DOI: 10.3389/fimmu.2014.00120
|View full text |Cite
|
Sign up to set email alerts
|

AIDing Chromatin and Transcription-Coupled Orchestration of Immunoglobulin Class-Switch Recombination

Abstract: Secondary diversification of the antibody repertoire upon antigenic challenge, in the form of immunoglobulin heavy chain (IgH) class-switch recombination (CSR) endows mature, naïve B cells in peripheral lymphoid organs with a limitless ability to mount an optimal humoral immune response, thus expediting pathogen elimination. CSR replaces the default constant (CH) region exons (Cμ) of IgH with any of the downstream CH exons (Cγ, Cε, or Cα), thereby altering effector functions of the antibody molecule. This proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 140 publications
(196 reference statements)
0
34
0
Order By: Relevance
“…Before the occurrence of DSBs, CSR is initiated by AID and the initial outcome of AID targeting can be the occurrence of base substitutions following cytidine deamination 12,14,15,21 . To gain an insight into this initial targeting, we analysed mutations in S regions and observed that both the S m donor and S g1 acceptor regions are less targeted by AID during IgG 1 CSR in 3 0 RR-deficient mice as compared with wt animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Before the occurrence of DSBs, CSR is initiated by AID and the initial outcome of AID targeting can be the occurrence of base substitutions following cytidine deamination 12,14,15,21 . To gain an insight into this initial targeting, we analysed mutations in S regions and observed that both the S m donor and S g1 acceptor regions are less targeted by AID during IgG 1 CSR in 3 0 RR-deficient mice as compared with wt animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3a). A crucial step of CSR is the processing of AID lesions into DSBs, as a specific feature of S regions 14,15 . Ligation-mediated PCR (LM-PCR, see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, this strand bias is reminiscent of transcription-coupled AID mutagenesis, which acts upon structures called R-loops, in which the non-coding strand is selectively looped out and deaminated while the coding strand is hybridized to the primary transcript and thus protected [71].…”
Section: Availability Of Ssdna Substratementioning
confidence: 99%